Supply chain integration and sustainable supply chain performance: a case of manufacturing firms from UAE - al Naqbi, Rashid Ahmed Khamis; Md Yusoff, Rosman; Ismail, Fadillah (American Scientific Publishers, 2018)
Sustainability is becoming a more important factor in the processes of organizations. Supply chains management (SCM) has acknowledged a great deal of interest by researchers and practitioners. The primary objective of the current research paper is to examine the relationship between internal integration and sustainable supply chain performance. In addition to that, the study has focused on the mediating effect of supplier integration and customer integration in the relationship between key between internal integration and sustainable supply chain performance. The study focuses on manufacturing enterprises of UAE under subject investigation and its relationship with sustainability goals. A detailed literature has been reviewed critically to develop the hypothesis of the study. A questionnaire survey was adopted to collect data from supply chain managers of manufacturing companies. Smart PLS 3 (SEM) is used to analyze the collected data. The results of the study have shown a great deal of agreement with the proposed hypothesis. Analysis of the study is divided into two major parts. Part one is based on an outer model assessment in which reliability and validity were examined. The second part is based on an inner model assessment in which hypotheses were tested. The result of the study will be useful for policymakers and researchers in understanding the emerging role of environmental concerns in strategic management and operational management.